Individual income tax as the object of taxation - Temirbekova, L.A.; Saduakassova, M.B.; Berdihojayeva, M.S. (BUKETOV BUSINESS REVIEW, 2017)
The article deals with the basic problems of individual income tax from the experience of foreign countries and the Republic of Kazakhstan. The authors studied the differences of individual income tax calculation in Kazakhstan and abroad. The authors reviewed the history of rate changes of individual income tax and social tax. The income of an individual from a tax agent, the income taxable at source of payment dealt with in accordance with the current Tax code of the Republic of Kazakhstan. In accordance with the Code defined by objects of taxation income tax. According to the Statistics Agency analyzed the structure and dynamics of tax revenues to the state budget of the country and made the appropriate conclusions. In different years has varied the calculation method of the calculation of the individual income tax and social tax. The calculation of the individual income tax has a direct affect change in the minimum wage. The article describes the change of minimum wage in Kazakhstan in recent years. In matters of individual income tax in the Republic of Kazakhstan is one of the complicated issues is the insufficient use in practice of the net income.